base-4.14.0.0: Basic libraries
Copyright(c) The University of Glasgow 2001
LicenseBSD-style (see the file libraries/base/LICENSE)
Maintainerlibraries@haskell.org
Stabilityprovisional
Portabilityportable
Safe HaskellTrustworthy
LanguageHaskell2010

Control.Monad

Description

The Functor, Monad and MonadPlus classes, with some useful operations on monads.

Synopsis

Functor and monad classes

class Functor f where Source #

A type f is a Functor if it provides a function fmap which, given any types a and b lets you apply any function from (a -> b) to turn an f a into an f b, preserving the structure of f. Furthermore f needs to adhere to the following:

Identity
fmap id == id
Composition
fmap (f . g) == fmap f . fmap g

Note, that the second law follows from the free theorem of the type fmap and the first law, so you need only check that the former condition holds.

Minimal complete definition

fmap

Methods

fmap :: (a -> b) -> f a -> f b Source #

Using ApplicativeDo: 'fmap f as' can be understood as the do expression

do a <- as
   pure (f a)

with an inferred Functor constraint.

(<$) :: a -> f b -> f a infixl 4 Source #

Replace all locations in the input with the same value. The default definition is fmap . const, but this may be overridden with a more efficient version.

Using ApplicativeDo: 'a <$ bs' can be understood as the do expression

do bs
   pure a

with an inferred Functor constraint.

Instances

Instances details
Functor [] #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> [a] -> [b] Source #

(<$) :: a -> [b] -> [a] Source #

Functor Maybe #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> Maybe a -> Maybe b Source #

(<$) :: a -> Maybe b -> Maybe a Source #

Functor IO #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> IO a -> IO b Source #

(<$) :: a -> IO b -> IO a Source #

Functor Par1 #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> Par1 a -> Par1 b Source #

(<$) :: a -> Par1 b -> Par1 a Source #

Functor NonEmpty #

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> NonEmpty a -> NonEmpty b Source #

(<$) :: a -> NonEmpty b -> NonEmpty a Source #

Functor NoIO #

Since: base-4.8.0.0

Instance details

Defined in GHC.GHCi

Methods

fmap :: (a -> b) -> NoIO a -> NoIO b Source #

(<$) :: a -> NoIO b -> NoIO a Source #

Functor ReadP #

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

fmap :: (a -> b) -> ReadP a -> ReadP b Source #

(<$) :: a -> ReadP b -> ReadP a Source #

Functor ReadPrec #

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadPrec

Methods

fmap :: (a -> b) -> ReadPrec a -> ReadPrec b Source #

(<$) :: a -> ReadPrec b -> ReadPrec a Source #

Functor Down #

Since: base-4.11.0.0

Instance details

Defined in Data.Ord

Methods

fmap :: (a -> b) -> Down a -> Down b Source #

(<$) :: a -> Down b -> Down a Source #

Functor Product #

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

fmap :: (a -> b) -> Product a -> Product b Source #

(<$) :: a -> Product b -> Product a Source #

Functor Sum #

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

fmap :: (a -> b) -> Sum a -> Sum b Source #

(<$) :: a -> Sum b -> Sum a Source #

Functor Dual #

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

fmap :: (a -> b) -> Dual a -> Dual b Source #

(<$) :: a -> Dual b -> Dual a Source #

Functor Last #

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

fmap :: (a -> b) -> Last a -> Last b Source #

(<$) :: a -> Last b -> Last a Source #

Functor First #

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

fmap :: (a -> b) -> First a -> First b Source #

(<$) :: a -> First b -> First a Source #

Functor STM #

Since: base-4.3.0.0

Instance details

Defined in GHC.Conc.Sync

Methods

fmap :: (a -> b) -> STM a -> STM b Source #

(<$) :: a -> STM b -> STM a Source #

Functor Handler #

Since: base-4.6.0.0

Instance details

Defined in Control.Exception

Methods

fmap :: (a -> b) -> Handler a -> Handler b Source #

(<$) :: a -> Handler b -> Handler a Source #

Functor Identity #

Since: base-4.8.0.0

Instance details

Defined in Data.Functor.Identity

Methods

fmap :: (a -> b) -> Identity a -> Identity b Source #

(<$) :: a -> Identity b -> Identity a Source #

Functor ZipList #

Since: base-2.1

Instance details

Defined in Control.Applicative

Methods

fmap :: (a -> b) -> ZipList a -> ZipList b Source #

(<$) :: a -> ZipList b -> ZipList a Source #

Functor ArgDescr #

Since: base-4.6.0.0

Instance details

Defined in System.Console.GetOpt

Methods

fmap :: (a -> b) -> ArgDescr a -> ArgDescr b Source #

(<$) :: a -> ArgDescr b -> ArgDescr a Source #

Functor OptDescr #

Since: base-4.6.0.0

Instance details

Defined in System.Console.GetOpt

Methods

fmap :: (a -> b) -> OptDescr a -> OptDescr b Source #

(<$) :: a -> OptDescr b -> OptDescr a Source #

Functor ArgOrder #

Since: base-4.6.0.0

Instance details

Defined in System.Console.GetOpt

Methods

fmap :: (a -> b) -> ArgOrder a -> ArgOrder b Source #

(<$) :: a -> ArgOrder b -> ArgOrder a Source #

Functor Option #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> Option a -> Option b Source #

(<$) :: a -> Option b -> Option a Source #

Functor Last #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> Last a -> Last b Source #

(<$) :: a -> Last b -> Last a Source #

Functor First #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> First a -> First b Source #

(<$) :: a -> First b -> First a Source #

Functor Max #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> Max a -> Max b Source #

(<$) :: a -> Max b -> Max a Source #

Functor Min #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> Min a -> Min b Source #

(<$) :: a -> Min b -> Min a Source #

Functor Complex #

Since: base-4.9.0.0

Instance details

Defined in Data.Complex

Methods

fmap :: (a -> b) -> Complex a -> Complex b Source #

(<$) :: a -> Complex b -> Complex a Source #

Functor (Either a) #

Since: base-3.0

Instance details

Defined in Data.Either

Methods

fmap :: (a0 -> b) -> Either a a0 -> Either a b Source #

(<$) :: a0 -> Either a b -> Either a a0 Source #

Functor (V1 :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> V1 a -> V1 b Source #

(<$) :: a -> V1 b -> V1 a Source #

Functor (U1 :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> U1 a -> U1 b Source #

(<$) :: a -> U1 b -> U1 a Source #

Functor ((,) a) #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a0 -> b) -> (a, a0) -> (a, b) Source #

(<$) :: a0 -> (a, b) -> (a, a0) Source #

Functor (ST s) #

Since: base-2.1

Instance details

Defined in GHC.ST

Methods

fmap :: (a -> b) -> ST s a -> ST s b Source #

(<$) :: a -> ST s b -> ST s a Source #

Functor (Array i) #

Since: base-2.1

Instance details

Defined in GHC.Arr

Methods

fmap :: (a -> b) -> Array i a -> Array i b Source #

(<$) :: a -> Array i b -> Array i a Source #

Functor (Proxy :: Type -> Type) #

Since: base-4.7.0.0

Instance details

Defined in Data.Proxy

Methods

fmap :: (a -> b) -> Proxy a -> Proxy b Source #

(<$) :: a -> Proxy b -> Proxy a Source #

Arrow a => Functor (ArrowMonad a) #

Since: base-4.6.0.0

Instance details

Defined in Control.Arrow

Methods

fmap :: (a0 -> b) -> ArrowMonad a a0 -> ArrowMonad a b Source #

(<$) :: a0 -> ArrowMonad a b -> ArrowMonad a a0 Source #

Monad m => Functor (WrappedMonad m) #

Since: base-2.1

Instance details

Defined in Control.Applicative

Methods

fmap :: (a -> b) -> WrappedMonad m a -> WrappedMonad m b Source #

(<$) :: a -> WrappedMonad m b -> WrappedMonad m a Source #

Functor (ST s) #

Since: base-2.1

Instance details

Defined in Control.Monad.ST.Lazy.Imp

Methods

fmap :: (a -> b) -> ST s a -> ST s b Source #

(<$) :: a -> ST s b -> ST s a Source #

Functor (Arg a) #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a0 -> b) -> Arg a a0 -> Arg a b Source #

(<$) :: a0 -> Arg a b -> Arg a a0 Source #

Functor f => Functor (Rec1 f) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> Rec1 f a -> Rec1 f b Source #

(<$) :: a -> Rec1 f b -> Rec1 f a Source #

Functor (URec Char :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> URec Char a -> URec Char b Source #

(<$) :: a -> URec Char b -> URec Char a Source #

Functor (URec Double :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> URec Double a -> URec Double b Source #

(<$) :: a -> URec Double b -> URec Double a Source #

Functor (URec Float :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> URec Float a -> URec Float b Source #

(<$) :: a -> URec Float b -> URec Float a Source #

Functor (URec Int :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> URec Int a -> URec Int b Source #

(<$) :: a -> URec Int b -> URec Int a Source #

Functor (URec Word :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> URec Word a -> URec Word b Source #

(<$) :: a -> URec Word b -> URec Word a Source #

Functor (URec (Ptr ()) :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> URec (Ptr ()) a -> URec (Ptr ()) b Source #

(<$) :: a -> URec (Ptr ()) b -> URec (Ptr ()) a Source #

Functor ((,,) a b) #

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

fmap :: (a0 -> b0) -> (a, b, a0) -> (a, b, b0) Source #

(<$) :: a0 -> (a, b, b0) -> (a, b, a0) Source #

Functor f => Functor (Alt f) #

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

fmap :: (a -> b) -> Alt f a -> Alt f b Source #

(<$) :: a -> Alt f b -> Alt f a Source #

Functor f => Functor (Ap f) #

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

fmap :: (a -> b) -> Ap f a -> Ap f b Source #

(<$) :: a -> Ap f b -> Ap f a Source #

Functor (Const m :: Type -> Type) #

Since: base-2.1

Instance details

Defined in Data.Functor.Const

Methods

fmap :: (a -> b) -> Const m a -> Const m b Source #

(<$) :: a -> Const m b -> Const m a Source #

Functor m => Functor (Kleisli m a) #

Since: base-4.14.0.0

Instance details

Defined in Control.Arrow

Methods

fmap :: (a0 -> b) -> Kleisli m a a0 -> Kleisli m a b Source #

(<$) :: a0 -> Kleisli m a b -> Kleisli m a a0 Source #

Arrow a => Functor (WrappedArrow a b) #

Since: base-2.1

Instance details

Defined in Control.Applicative

Methods

fmap :: (a0 -> b0) -> WrappedArrow a b a0 -> WrappedArrow a b b0 Source #

(<$) :: a0 -> WrappedArrow a b b0 -> WrappedArrow a b a0 Source #

Functor ((->) r :: Type -> Type) #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> (r -> a) -> r -> b Source #

(<$) :: a -> (r -> b) -> r -> a Source #

Functor (K1 i a :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a0 -> b) -> K1 i a a0 -> K1 i a b Source #

(<$) :: a0 -> K1 i a b -> K1 i a a0 Source #

(Functor f, Functor g) => Functor (f :+: g) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> (f :+: g) a -> (f :+: g) b Source #

(<$) :: a -> (f :+: g) b -> (f :+: g) a Source #

(Functor f, Functor g) => Functor (f :*: g) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> (f :*: g) a -> (f :*: g) b Source #

(<$) :: a -> (f :*: g) b -> (f :*: g) a Source #

Functor ((,,,) a b c) #

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

fmap :: (a0 -> b0) -> (a, b, c, a0) -> (a, b, c, b0) Source #

(<$) :: a0 -> (a, b, c, b0) -> (a, b, c, a0) Source #

(Functor f, Functor g) => Functor (Sum f g) #

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Sum

Methods

fmap :: (a -> b) -> Sum f g a -> Sum f g b Source #

(<$) :: a -> Sum f g b -> Sum f g a Source #

(Functor f, Functor g) => Functor (Product f g) #

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Product

Methods

fmap :: (a -> b) -> Product f g a -> Product f g b Source #

(<$) :: a -> Product f g b -> Product f g a Source #

Functor f => Functor (M1 i meta f) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> M1 i meta f a -> M1 i meta f b Source #

(<$) :: a -> M1 i meta f b -> M1 i meta f a Source #

(Functor f, Functor g) => Functor (f :.: g) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

fmap :: (a -> b) -> (f :.: g) a -> (f :.: g) b Source #

(<$) :: a -> (f :.: g) b -> (f :.: g) a Source #

(Functor f, Functor g) => Functor (Compose f g) #

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Compose

Methods

fmap :: (a -> b) -> Compose f g a -> Compose f g b Source #

(<$) :: a -> Compose f g b -> Compose f g a Source #

class Applicative m => Monad m where Source #

The Monad class defines the basic operations over a monad, a concept from a branch of mathematics known as category theory. From the perspective of a Haskell programmer, however, it is best to think of a monad as an abstract datatype of actions. Haskell's do expressions provide a convenient syntax for writing monadic expressions.

Instances of Monad should satisfy the following:

Left identity
return a >>= k = k a
Right identity
m >>= return = m
Associativity
m >>= (\x -> k x >>= h) = (m >>= k) >>= h

Furthermore, the Monad and Applicative operations should relate as follows:

The above laws imply:

and that pure and (<*>) satisfy the applicative functor laws.

The instances of Monad for lists, Maybe and IO defined in the Prelude satisfy these laws.

Minimal complete definition

(>>=)

Methods

(>>=) :: forall a b. m a -> (a -> m b) -> m b infixl 1 Source #

Sequentially compose two actions, passing any value produced by the first as an argument to the second.

'as >>= bs' can be understood as the do expression

do a <- as
   bs a

(>>) :: forall a b. m a -> m b -> m b infixl 1 Source #

Sequentially compose two actions, discarding any value produced by the first, like sequencing operators (such as the semicolon) in imperative languages.

'as >> bs' can be understood as the do expression

do as
   bs

return :: a -> m a Source #

Inject a value into the monadic type.

Instances

Instances details
Monad [] #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: [a] -> (a -> [b]) -> [b] Source #

(>>) :: [a] -> [b] -> [b] Source #

return :: a -> [a] Source #

Monad Maybe #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: Maybe a -> (a -> Maybe b) -> Maybe b Source #

(>>) :: Maybe a -> Maybe b -> Maybe b Source #

return :: a -> Maybe a Source #

Monad IO #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: IO a -> (a -> IO b) -> IO b Source #

(>>) :: IO a -> IO b -> IO b Source #

return :: a -> IO a Source #

Monad Par1 #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

(>>=) :: Par1 a -> (a -> Par1 b) -> Par1 b Source #

(>>) :: Par1 a -> Par1 b -> Par1 b Source #

return :: a -> Par1 a Source #

Monad NonEmpty #

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: NonEmpty a -> (a -> NonEmpty b) -> NonEmpty b Source #

(>>) :: NonEmpty a -> NonEmpty b -> NonEmpty b Source #

return :: a -> NonEmpty a Source #

Monad NoIO #

Since: base-4.4.0.0

Instance details

Defined in GHC.GHCi

Methods

(>>=) :: NoIO a -> (a -> NoIO b) -> NoIO b Source #

(>>) :: NoIO a -> NoIO b -> NoIO b Source #

return :: a -> NoIO a Source #

Monad ReadP #

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

(>>=) :: ReadP a -> (a -> ReadP b) -> ReadP b Source #

(>>) :: ReadP a -> ReadP b -> ReadP b Source #

return :: a -> ReadP a Source #

Monad ReadPrec #

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadPrec

Methods

(>>=) :: ReadPrec a -> (a -> ReadPrec b) -> ReadPrec b Source #

(>>) :: ReadPrec a -> ReadPrec b -> ReadPrec b Source #

return :: a -> ReadPrec a Source #

Monad Down #

Since: base-4.11.0.0

Instance details

Defined in Data.Ord

Methods

(>>=) :: Down a -> (a -> Down b) -> Down b Source #

(>>) :: Down a -> Down b -> Down b Source #

return :: a -> Down a Source #

Monad Product #

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Product a -> (a -> Product b) -> Product b Source #

(>>) :: Product a -> Product b -> Product b Source #

return :: a -> Product a Source #

Monad Sum #

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Sum a -> (a -> Sum b) -> Sum b Source #

(>>) :: Sum a -> Sum b -> Sum b Source #

return :: a -> Sum a Source #

Monad Dual #

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Dual a -> (a -> Dual b) -> Dual b Source #

(>>) :: Dual a -> Dual b -> Dual b Source #

return :: a -> Dual a Source #

Monad Last #

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

(>>=) :: Last a -> (a -> Last b) -> Last b Source #

(>>) :: Last a -> Last b -> Last b Source #

return :: a -> Last a Source #

Monad First #

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

(>>=) :: First a -> (a -> First b) -> First b Source #

(>>) :: First a -> First b -> First b Source #

return :: a -> First a Source #

Monad STM #

Since: base-4.3.0.0

Instance details

Defined in GHC.Conc.Sync

Methods

(>>=) :: STM a -> (a -> STM b) -> STM b Source #

(>>) :: STM a -> STM b -> STM b Source #

return :: a -> STM a Source #

Monad Identity #

Since: base-4.8.0.0

Instance details

Defined in Data.Functor.Identity

Methods

(>>=) :: Identity a -> (a -> Identity b) -> Identity b Source #

(>>) :: Identity a -> Identity b -> Identity b Source #

return :: a -> Identity a Source #

Monad Option #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Option a -> (a -> Option b) -> Option b Source #

(>>) :: Option a -> Option b -> Option b Source #

return :: a -> Option a Source #

Monad Last #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Last a -> (a -> Last b) -> Last b Source #

(>>) :: Last a -> Last b -> Last b Source #

return :: a -> Last a Source #

Monad First #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: First a -> (a -> First b) -> First b Source #

(>>) :: First a -> First b -> First b Source #

return :: a -> First a Source #

Monad Max #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Max a -> (a -> Max b) -> Max b Source #

(>>) :: Max a -> Max b -> Max b Source #

return :: a -> Max a Source #

Monad Min #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Min a -> (a -> Min b) -> Min b Source #

(>>) :: Min a -> Min b -> Min b Source #

return :: a -> Min a Source #

Monad Complex #

Since: base-4.9.0.0

Instance details

Defined in Data.Complex

Methods

(>>=) :: Complex a -> (a -> Complex b) -> Complex b Source #

(>>) :: Complex a -> Complex b -> Complex b Source #

return :: a -> Complex a Source #

Monad (Either e) #

Since: base-4.4.0.0

Instance details

Defined in Data.Either

Methods

(>>=) :: Either e a -> (a -> Either e b) -> Either e b Source #

(>>) :: Either e a -> Either e b -> Either e b Source #

return :: a -> Either e a Source #

Monad (U1 :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

(>>=) :: U1 a -> (a -> U1 b) -> U1 b Source #

(>>) :: U1 a -> U1 b -> U1 b Source #

return :: a -> U1 a Source #

Monoid a => Monad ((,) a) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: (a, a0) -> (a0 -> (a, b)) -> (a, b) Source #

(>>) :: (a, a0) -> (a, b) -> (a, b) Source #

return :: a0 -> (a, a0) Source #

Monad (ST s) #

Since: base-2.1

Instance details

Defined in GHC.ST

Methods

(>>=) :: ST s a -> (a -> ST s b) -> ST s b Source #

(>>) :: ST s a -> ST s b -> ST s b Source #

return :: a -> ST s a Source #

Monad (Proxy :: Type -> Type) #

Since: base-4.7.0.0

Instance details

Defined in Data.Proxy

Methods

(>>=) :: Proxy a -> (a -> Proxy b) -> Proxy b Source #

(>>) :: Proxy a -> Proxy b -> Proxy b Source #

return :: a -> Proxy a Source #

ArrowApply a => Monad (ArrowMonad a) #

Since: base-2.1

Instance details

Defined in Control.Arrow

Methods

(>>=) :: ArrowMonad a a0 -> (a0 -> ArrowMonad a b) -> ArrowMonad a b Source #

(>>) :: ArrowMonad a a0 -> ArrowMonad a b -> ArrowMonad a b Source #

return :: a0 -> ArrowMonad a a0 Source #

Monad m => Monad (WrappedMonad m) #

Since: base-4.7.0.0

Instance details

Defined in Control.Applicative

Methods

(>>=) :: WrappedMonad m a -> (a -> WrappedMonad m b) -> WrappedMonad m b Source #

(>>) :: WrappedMonad m a -> WrappedMonad m b -> WrappedMonad m b Source #

return :: a -> WrappedMonad m a Source #

Monad (ST s) #

Since: base-2.1

Instance details

Defined in Control.Monad.ST.Lazy.Imp

Methods

(>>=) :: ST s a -> (a -> ST s b) -> ST s b Source #

(>>) :: ST s a -> ST s b -> ST s b Source #

return :: a -> ST s a Source #

Monad f => Monad (Rec1 f) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

(>>=) :: Rec1 f a -> (a -> Rec1 f b) -> Rec1 f b Source #

(>>) :: Rec1 f a -> Rec1 f b -> Rec1 f b Source #

return :: a -> Rec1 f a Source #

(Monoid a, Monoid b) => Monad ((,,) a b) #

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: (a, b, a0) -> (a0 -> (a, b, b0)) -> (a, b, b0) Source #

(>>) :: (a, b, a0) -> (a, b, b0) -> (a, b, b0) Source #

return :: a0 -> (a, b, a0) Source #

Monad f => Monad (Alt f) #

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Alt f a -> (a -> Alt f b) -> Alt f b Source #

(>>) :: Alt f a -> Alt f b -> Alt f b Source #

return :: a -> Alt f a Source #

Monad f => Monad (Ap f) #

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

(>>=) :: Ap f a -> (a -> Ap f b) -> Ap f b Source #

(>>) :: Ap f a -> Ap f b -> Ap f b Source #

return :: a -> Ap f a Source #

Monad m => Monad (Kleisli m a) #

Since: base-4.14.0.0

Instance details

Defined in Control.Arrow

Methods

(>>=) :: Kleisli m a a0 -> (a0 -> Kleisli m a b) -> Kleisli m a b Source #

(>>) :: Kleisli m a a0 -> Kleisli m a b -> Kleisli m a b Source #

return :: a0 -> Kleisli m a a0 Source #

Monad ((->) r :: Type -> Type) #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: (r -> a) -> (a -> r -> b) -> r -> b Source #

(>>) :: (r -> a) -> (r -> b) -> r -> b Source #

return :: a -> r -> a Source #

(Monad f, Monad g) => Monad (f :*: g) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

(>>=) :: (f :*: g) a -> (a -> (f :*: g) b) -> (f :*: g) b Source #

(>>) :: (f :*: g) a -> (f :*: g) b -> (f :*: g) b Source #

return :: a -> (f :*: g) a Source #

(Monoid a, Monoid b, Monoid c) => Monad ((,,,) a b c) #

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: (a, b, c, a0) -> (a0 -> (a, b, c, b0)) -> (a, b, c, b0) Source #

(>>) :: (a, b, c, a0) -> (a, b, c, b0) -> (a, b, c, b0) Source #

return :: a0 -> (a, b, c, a0) Source #

(Monad f, Monad g) => Monad (Product f g) #

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Product

Methods

(>>=) :: Product f g a -> (a -> Product f g b) -> Product f g b Source #

(>>) :: Product f g a -> Product f g b -> Product f g b Source #

return :: a -> Product f g a Source #

Monad f => Monad (M1 i c f) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

(>>=) :: M1 i c f a -> (a -> M1 i c f b) -> M1 i c f b Source #

(>>) :: M1 i c f a -> M1 i c f b -> M1 i c f b Source #

return :: a -> M1 i c f a Source #

class Monad m => MonadFail m where Source #

When a value is bound in do-notation, the pattern on the left hand side of <- might not match. In this case, this class provides a function to recover.

A Monad without a MonadFail instance may only be used in conjunction with pattern that always match, such as newtypes, tuples, data types with only a single data constructor, and irrefutable patterns (~pat).

Instances of MonadFail should satisfy the following law: fail s should be a left zero for >>=,

fail s >>= f  =  fail s

If your Monad is also MonadPlus, a popular definition is

fail _ = mzero

Since: base-4.9.0.0

Methods

fail :: String -> m a Source #

Instances

Instances details
MonadFail [] #

Since: base-4.9.0.0

Instance details

Defined in Control.Monad.Fail

Methods

fail :: String -> [a] Source #

MonadFail Maybe #

Since: base-4.9.0.0

Instance details

Defined in Control.Monad.Fail

Methods

fail :: String -> Maybe a Source #

MonadFail IO #

Since: base-4.9.0.0

Instance details

Defined in Control.Monad.Fail

Methods

fail :: String -> IO a Source #

MonadFail ReadP #

Since: base-4.9.0.0

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

fail :: String -> ReadP a Source #

MonadFail ReadPrec #

Since: base-4.9.0.0

Instance details

Defined in Text.ParserCombinators.ReadPrec

Methods

fail :: String -> ReadPrec a Source #

MonadFail (ST s) #

Since: base-4.11.0.0

Instance details

Defined in GHC.ST

Methods

fail :: String -> ST s a Source #

MonadFail (ST s) #

Since: base-4.10

Instance details

Defined in Control.Monad.ST.Lazy.Imp

Methods

fail :: String -> ST s a Source #

MonadFail f => MonadFail (Ap f) #

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

fail :: String -> Ap f a Source #

class (Alternative m, Monad m) => MonadPlus m where Source #

Monads that also support choice and failure.

Minimal complete definition

Nothing

Methods

mzero :: m a Source #

The identity of mplus. It should also satisfy the equations

mzero >>= f  =  mzero
v >> mzero   =  mzero

The default definition is

mzero = empty

mplus :: m a -> m a -> m a Source #

An associative operation. The default definition is

mplus = (<|>)

Instances

Instances details
MonadPlus [] #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

mzero :: [a] Source #

mplus :: [a] -> [a] -> [a] Source #

MonadPlus Maybe #

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

mzero :: Maybe a Source #

mplus :: Maybe a -> Maybe a -> Maybe a Source #

MonadPlus IO #

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

mzero :: IO a Source #

mplus :: IO a -> IO a -> IO a Source #

MonadPlus ReadP #

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

mzero :: ReadP a Source #

mplus :: ReadP a -> ReadP a -> ReadP a Source #

MonadPlus ReadPrec #

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadPrec

MonadPlus STM #

Since: base-4.3.0.0

Instance details

Defined in GHC.Conc.Sync

Methods

mzero :: STM a Source #

mplus :: STM a -> STM a -> STM a Source #

MonadPlus Option #

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

mzero :: Option a Source #

mplus :: Option a -> Option a -> Option a Source #

MonadPlus (U1 :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

mzero :: U1 a Source #

mplus :: U1 a -> U1 a -> U1 a Source #

MonadPlus (Proxy :: Type -> Type) #

Since: base-4.9.0.0

Instance details

Defined in Data.Proxy

Methods

mzero :: Proxy a Source #

mplus :: Proxy a -> Proxy a -> Proxy a Source #

(ArrowApply a, ArrowPlus a) => MonadPlus (ArrowMonad a) #

Since: base-4.6.0.0

Instance details

Defined in Control.Arrow

Methods

mzero :: ArrowMonad a a0 Source #

mplus :: ArrowMonad a a0 -> ArrowMonad a a0 -> ArrowMonad a a0 Source #

MonadPlus f => MonadPlus (Rec1 f) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

mzero :: Rec1 f a Source #

mplus :: Rec1 f a -> Rec1 f a -> Rec1 f a Source #

MonadPlus f => MonadPlus (Alt f) #

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

mzero :: Alt f a Source #

mplus :: Alt f a -> Alt f a -> Alt f a Source #

MonadPlus f => MonadPlus (Ap f) #

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

mzero :: Ap f a Source #

mplus :: Ap f a -> Ap f a -> Ap f a Source #

MonadPlus m => MonadPlus (Kleisli m a) #

Since: base-4.14.0.0

Instance details

Defined in Control.Arrow

Methods

mzero :: Kleisli m a a0 Source #

mplus :: Kleisli m a a0 -> Kleisli m a a0 -> Kleisli m a a0 Source #

(MonadPlus f, MonadPlus g) => MonadPlus (f :*: g) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

mzero :: (f :*: g) a Source #

mplus :: (f :*: g) a -> (f :*: g) a -> (f :*: g) a Source #

(MonadPlus f, MonadPlus g) => MonadPlus (Product f g) #

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Product

Methods

mzero :: Product f g a Source #

mplus :: Product f g a -> Product f g a -> Product f g a Source #

MonadPlus f => MonadPlus (M1 i c f) #

Since: base-4.9.0.0

Instance details

Defined in GHC.Generics

Methods

mzero :: M1 i c f a Source #

mplus :: M1 i c f a -> M1 i c f a -> M1 i c f a Source #

Functions

Naming conventions

The functions in this library use the following naming conventions:

  • A postfix 'M' always stands for a function in the Kleisli category: The monad type constructor m is added to function results (modulo currying) and nowhere else. So, for example,
filter  ::              (a ->   Bool) -> [a] ->   [a]
filterM :: (Monad m) => (a -> m Bool) -> [a] -> m [a]
  • A postfix '_' changes the result type from (m a) to (m ()). Thus, for example:
sequence  :: Monad m => [m a] -> m [a]
sequence_ :: Monad m => [m a] -> m ()
  • A prefix 'm' generalizes an existing function to a monadic form. Thus, for example:
filter  ::                (a -> Bool) -> [a] -> [a]
mfilter :: MonadPlus m => (a -> Bool) -> m a -> m a

Basic Monad functions

mapM :: (Traversable t, Monad m) => (a -> m b) -> t a -> m (t b) Source #

Map each element of a structure to a monadic action, evaluate these actions from left to right, and collect the results. For a version that ignores the results see mapM_.

mapM_ :: (Foldable t, Monad m) => (a -> m b) -> t a -> m () Source #

Map each element of a structure to a monadic action, evaluate these actions from left to right, and ignore the results. For a version that doesn't ignore the results see mapM.

As of base 4.8.0.0, mapM_ is just traverse_, specialized to Monad.

forM :: (Traversable t, Monad m) => t a -> (a -> m b) -> m (t b) Source #

forM is mapM with its arguments flipped. For a version that ignores the results see forM_.

forM_ :: (Foldable t, Monad m) => t a -> (a -> m b) -> m () Source #

forM_ is mapM_ with its arguments flipped. For a version that doesn't ignore the results see forM.

As of base 4.8.0.0, forM_ is just for_, specialized to Monad.

sequence :: (Traversable t, Monad m) => t (m a) -> m (t a) Source #

Evaluate each monadic action in the structure from left to right, and collect the results. For a version that ignores the results see sequence_.

sequence_ :: (Foldable t, Monad m) => t (m a) -> m () Source #

Evaluate each monadic action in the structure from left to right, and ignore the results. For a version that doesn't ignore the results see sequence.

As of base 4.8.0.0, sequence_ is just sequenceA_, specialized to Monad.

(=<<) :: Monad m => (a -> m b) -> m a -> m b infixr 1 Source #

Same as >>=, but with the arguments interchanged.

(>=>) :: Monad m => (a -> m b) -> (b -> m c) -> a -> m c infixr 1 Source #

Left-to-right composition of Kleisli arrows.

'(bs >=> cs) a' can be understood as the do expression

do b <- bs a
   cs b

(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> a -> m c infixr 1 Source #

Right-to-left composition of Kleisli arrows. (>=>), with the arguments flipped.

Note how this operator resembles function composition (.):

(.)   ::            (b ->   c) -> (a ->   b) -> a ->   c
(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> a -> m c

forever :: Applicative f => f a -> f b Source #

Repeat an action indefinitely.

Using ApplicativeDo: 'forever as' can be understood as the pseudo-do expression

do as
   as
   ..

with as repeating.

Examples

Expand

A common use of forever is to process input from network sockets, Handles, and channels (e.g. MVar and Chan).

For example, here is how we might implement an echo server, using forever both to listen for client connections on a network socket and to echo client input on client connection handles:

echoServer :: Socket -> IO ()
echoServer socket = forever $ do
  client <- accept socket
  forkFinally (echo client) (\_ -> hClose client)
  where
    echo :: Handle -> IO ()
    echo client = forever $
      hGetLine client >>= hPutStrLn client

void :: Functor f => f a -> f () Source #

void value discards or ignores the result of evaluation, such as the return value of an IO action.

Using ApplicativeDo: 'void as' can be understood as the do expression

do as
   pure ()

with an inferred Functor constraint.

Examples

Expand

Replace the contents of a Maybe Int with unit:

>>> void Nothing
Nothing
>>> void (Just 3)
Just ()

Replace the contents of an Either Int Int with unit, resulting in an Either Int '()':

>>> void (Left 8675309)
Left 8675309
>>> void (Right 8675309)
Right ()

Replace every element of a list with unit:

>>> void [1,2,3]
[(),(),()]

Replace the second element of a pair with unit:

>>> void (1,2)
(1,())

Discard the result of an IO action:

>>> mapM print [1,2]
1
2
[(),()]
>>> void $ mapM print [1,2]
1
2

Generalisations of list functions

join :: Monad m => m (m a) -> m a Source #

The join function is the conventional monad join operator. It is used to remove one level of monadic structure, projecting its bound argument into the outer level.

'join bss' can be understood as the do expression

do bs <- bss
   bs

Examples

Expand

A common use of join is to run an IO computation returned from an STM transaction, since STM transactions can't perform IO directly. Recall that

atomically :: STM a -> IO a

is used to run STM transactions atomically. So, by specializing the types of atomically and join to

atomically :: STM (IO b) -> IO (IO b)
join       :: IO (IO b)  -> IO b

we can compose them as

join . atomically :: STM (IO b) -> IO b

to run an STM transaction and the IO action it returns.

msum :: (Foldable t, MonadPlus m) => t (m a) -> m a Source #

The sum of a collection of actions, generalizing concat. As of base 4.8.0.0, msum is just asum, specialized to MonadPlus.

mfilter :: MonadPlus m => (a -> Bool) -> m a -> m a Source #

Direct MonadPlus equivalent of filter.

Examples

Expand

The filter function is just mfilter specialized to the list monad:

filter = ( mfilter :: (a -> Bool) -> [a] -> [a] )

An example using mfilter with the Maybe monad:

>>> mfilter odd (Just 1)
Just 1
>>> mfilter odd (Just 2)
Nothing

filterM :: Applicative m => (a -> m Bool) -> [a] -> m [a] Source #

This generalizes the list-based filter function.

mapAndUnzipM :: Applicative m => (a -> m (b, c)) -> [a] -> m ([b], [c]) Source #

The mapAndUnzipM function maps its first argument over a list, returning the result as a pair of lists. This function is mainly used with complicated data structures or a state monad.

zipWithM :: Applicative m => (a -> b -> m c) -> [a] -> [b] -> m [c] Source #

The zipWithM function generalizes zipWith to arbitrary applicative functors.

zipWithM_ :: Applicative m => (a -> b -> m c) -> [a] -> [b] -> m () Source #

zipWithM_ is the extension of zipWithM which ignores the final result.

foldM :: (Foldable t, Monad m) => (b -> a -> m b) -> b -> t a -> m b Source #

The foldM function is analogous to foldl, except that its result is encapsulated in a monad. Note that foldM works from left-to-right over the list arguments. This could be an issue where (>>) and the `folded function' are not commutative.

foldM f a1 [x1, x2, ..., xm]

==

do
  a2 <- f a1 x1
  a3 <- f a2 x2
  ...
  f am xm

If right-to-left evaluation is required, the input list should be reversed.

Note: foldM is the same as foldlM

foldM_ :: (Foldable t, Monad m) => (b -> a -> m b) -> b -> t a -> m () Source #

Like foldM, but discards the result.

replicateM :: Applicative m => Int -> m a -> m [a] Source #

replicateM n act performs the action n times, gathering the results.

Using ApplicativeDo: 'replicateM 5 as' can be understood as the do expression

do a1 <- as
   a2 <- as
   a3 <- as
   a4 <- as
   a5 <- as
   pure [a1,a2,a3,a4,a5]

Note the Applicative constraint.

replicateM_ :: Applicative m => Int -> m a -> m () Source #

Like replicateM, but discards the result.

Conditional execution of monadic expressions

guard :: Alternative f => Bool -> f () Source #

Conditional failure of Alternative computations. Defined by

guard True  = pure ()
guard False = empty

Examples

Expand

Common uses of guard include conditionally signaling an error in an error monad and conditionally rejecting the current choice in an Alternative-based parser.

As an example of signaling an error in the error monad Maybe, consider a safe division function safeDiv x y that returns Nothing when the denominator y is zero and Just (x `div` y) otherwise. For example:

>>> safeDiv 4 0
Nothing
>>> safeDiv 4 2
Just 2

A definition of safeDiv using guards, but not guard:

safeDiv :: Int -> Int -> Maybe Int
safeDiv x y | y /= 0    = Just (x `div` y)
            | otherwise = Nothing

A definition of safeDiv using guard and Monad do-notation:

safeDiv :: Int -> Int -> Maybe Int
safeDiv x y = do
  guard (y /= 0)
  return (x `div` y)

when :: Applicative f => Bool -> f () -> f () Source #

Conditional execution of Applicative expressions. For example,

when debug (putStrLn "Debugging")

will output the string Debugging if the Boolean value debug is True, and otherwise do nothing.

unless :: Applicative f => Bool -> f () -> f () Source #

The reverse of when.

Monadic lifting operators

liftM :: Monad m => (a1 -> r) -> m a1 -> m r Source #

Promote a function to a monad.

liftM2 :: Monad m => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r Source #

Promote a function to a monad, scanning the monadic arguments from left to right. For example,

liftM2 (+) [0,1] [0,2] = [0,2,1,3]
liftM2 (+) (Just 1) Nothing = Nothing

liftM3 :: Monad m => (a1 -> a2 -> a3 -> r) -> m a1 -> m a2 -> m a3 -> m r Source #

Promote a function to a monad, scanning the monadic arguments from left to right (cf. liftM2).

liftM4 :: Monad m => (a1 -> a2 -> a3 -> a4 -> r) -> m a1 -> m a2 -> m a3 -> m a4 -> m r Source #

Promote a function to a monad, scanning the monadic arguments from left to right (cf. liftM2).

liftM5 :: Monad m => (a1 -> a2 -> a3 -> a4 -> a5 -> r) -> m a1 -> m a2 -> m a3 -> m a4 -> m a5 -> m r Source #

Promote a function to a monad, scanning the monadic arguments from left to right (cf. liftM2).

ap :: Monad m => m (a -> b) -> m a -> m b Source #

In many situations, the liftM operations can be replaced by uses of ap, which promotes function application.

return f `ap` x1 `ap` ... `ap` xn

is equivalent to

liftMn f x1 x2 ... xn

Strict monadic functions

(<$!>) :: Monad m => (a -> b) -> m a -> m b infixl 4 Source #

Strict version of <$>.

Since: base-4.8.0.0